The Arch, Adams Square, 1930 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking southwest from Faneuil Hall toward Dock and Adams Squares. Spectators are watching a procession of Legionnaires in the National American Legion parade turning onto Congress Street from Adams Square. Spectators can also been seen watching the parade from the windows of buildings lining the route. 7 1/2 x 9 7/16 overall 8 x 10 Photographs